Transformational Leadership: Principal Intellectual Stimulation In Improving Teacher Competences - Makherus Sholeh (Institut Agama Islam Negeri Imam Bonjol Padang, 2021)
Various efforts have been made to improve teacher competence, but there are still many institutions that have not optimized teacher capacity development. This study examines the intellectual stimulation of principals in improving teacher competence in two favorite institutions in the East Java region of SDI Qurrota A'yun Tulungagung and MI Perwanida Blitar. This study uses a qualitative descriptive method with a multi-case study design. Data were collected through 16 teachers and one school committee, one student guardian, one community leader, and one employee determined by random purposive sampling. Information was obtained through interviews, documentation, and observation. The results of this study indicate the role of leaders in forming various teacher competency improvement programs; (a) Program in-service education. The leader delegates teachers to improve professional and pedagogical competencies, which consist of advanced study programs, equivalency studies, Teacher Professional Education (PPG), (b) Program in-service training. Leaders delegate teachers to improve pedagogical and professional competencies through training activities, seminars, workshops, and webinars. (c) Leaders conducted program on-service training as a facility to improve teacher competence, (1) Supervision Activities and Teacher Working Groups (KKG), (2) teachers are actively competing, (3) actively writing papers, (4) collaboration activity, (5) social service activities, (6) religious activity (7) Job rotation, (8) Curriculum integration according to the institution's development distinction, (9) Technology-based learning.